2023
DOI: 10.3390/agriculture13051047
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Going Green? Determinants of Green Investment Intention in the Saudi Food Industry

Abstract: The Kingdom of Saudi Arabia (KSA) has witnessed major transformations in social, economic, and environmental aspects since the inauguration of Saudi Vision 2030 in April 2016. In alignment with this, the leadership of KSA has inaugurated green initiatives that pave the way for green investment opportunities in different industries within KSA. However, there was limited, if any, research about green investment intention and behaviour in KSA. This research tests an expanded model of the Theory of Planned Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…When leaders are committed to sustainability, it often permeates throughout the organization [ 19 ]. It is also found that firms with strong research and development capabilities may be more inclined to invest in innovative green technologies and solutions [ 17 ]. Companies aiming to improve operational efficiency may invest in green initiatives to reduce energy consumption, waste, and resource use, which can lead to cost savings [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When leaders are committed to sustainability, it often permeates throughout the organization [ 19 ]. It is also found that firms with strong research and development capabilities may be more inclined to invest in innovative green technologies and solutions [ 17 ]. Companies aiming to improve operational efficiency may invest in green initiatives to reduce energy consumption, waste, and resource use, which can lead to cost savings [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consumer and market demand for environmentally friendly products and services can drive firms to invest in green initiatives [ 17 ]. Meeting these demands can lead to competitive advantages and increased market share.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with a body of literature that shows that a person can manage their finances more effectively the more education they have. As a result, they will favor investments that are more sustainable [15], [19], [24].…”
Section: Resultsmentioning
confidence: 99%
“…This kind of investment benefits the environment by lowering greenhouse gas emissions and air pollution while upholding the standard of production and consumption. New programs and technology are adopted by the green investing industry to guarantee environmental sustainability [15]. Implementation of new technology implies higher risk assumed by the companies because of the uncertainty of the project's success.…”
Section: Financial Literacy and Green Investmentmentioning
confidence: 99%